Gender Dimensions of Food Security and Agricultural Productivity: A Regional Geography Analysis of West Java - Maman Sulaeman; Khalid Eltayeb Elfaki (JAMBURA GEO EDUCATION JOURNAL, 2026)
The interconnected dynamics of agricultural productivity and gender equity present complex challenges and opportunities for food security in agrarian regions. In Indonesia, West Java is a leading rice producer, yet food security disparities persist, highlighting the need to examine both production capacity and gender development. This study analyzes the impact of rice harvested area and the Gender Development Index (GDI) on food security across 27 districts/cities in West Java from 2018 to 2022. Using panel data and fixed-effects regression, the study evaluates both additive and interaction effects while controlling for GDP per capita, poverty, and population. The interaction model explains substantial variation (R² = 0.721). Rice harvested area (β = 0.024) and GDI (β = 30.874) each positively influence food security. The interaction term (β = 0.087) confirms that higher gender development strengthens the positive impact of agricultural production. Marginal analysis indicates that increases in rice production have stronger effects in high-GDI regions, where women have greater access to resources and economic opportunities. Conversely, poverty negatively affects food security (β = −0.281), limiting household access to food regardless of production levels. These findings suggest that uniform agricultural policies are insufficient. High-GDI regions should prioritize value-chain development and income diversification, while low-GDI regions require simultaneous investment in agricultural capacity and women’s empowerment. Achieving equitable and sustainable food security requires integrated policies that balance agricultural development with gender equality